Gambaran Perilaku Menggosok Gigi pada Anak Usia Sekolah di SD Pertiwi Kota Makassar - Hasrini Hasrini; Zahrawi Astrie Ahkam; Amirah Maritsa; Suciyati Sundu; Dewi Sartika (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Dental and oral hygiene is when there is no dirt and dental caries in the mouth. This is due to the fact that children in schools do not understand the effects of not brushing their teeth which can affect the body's metabolism. Preliminary research at SD Pertiwi showed that some school-age children do not understand the behavior of brushing their teeth. The purpose of this study was to determine how the behavior of brushing teeth at school age at SD Pertiwi. This study was designed to use a quantitative descriptive method. This study involved all students of SD Pertiwi, totaling 89 male and female students, and the sampling technique was random sampling. The research method was a questionnaire, consisting of 18 questions. Univariate analysis was used to analyze the data. The results showed that school-age children at SD Pertiwi Besar had good behavior when brushing their teeth (92.1%) and bad behavior as much as 7.9%.